Is there an association between airborne and surface microbes in the critical care environment?. Issue 3 (November 2018) - Smith, J.; Adams, C.E.; King, M.F.; Noakes, C.J.; Robertson, C.; Dancer, S.J.
Summary: Background: There are few data and no accepted standards for air quality in the intensive care unit (ICU). Any relationship between airborne pathogens and hospital-acquired infection (HAI) risk in the ICU remains unknown. Aim: First, to correlate environmental contamination of air and surfaces in the ICU; second, to examine any association between environmental contamination and ICU-acquired staphylococcal infection. Methods: Patients, air, and surfaces were screened on 10 sampling days in a mechanically ventilated 10-bed ICU for a 10-month period. Near-patient hand-touch sites ( N  = 500) and air ( N  = 80) were screened for total colony count and Staphylococcus aureus . Air counts were compared with surface counts according to proposed standards for air and surface bioburden. Patients were monitored for ICU-acquired staphylococcal infection throughout. Findings: Overall, 235 of 500 (47%) surfaces failed the standard for aerobic counts (≤2.5 cfu/cm 2 ). Half of passive air samples (20/40: 50%) failed the 'index of microbial air' contamination (2 cfu/9 cm plate/h), and 15/40 (37.5%) active air samples failed the clean air standard (<10 cfu/m 3 ). Settle plate data were closer to the pass/fail proportion from surfaces and provided the best agreement between air parameters and surfaces when evaluating surface benchmark values of 0–20 cfu/cm 2 . The surface standard most likely to reflect hygiene pass/fail results compared with air was 5 cfu/cm 2 . Rates of ICU-acquired staphylococcal infection were associated with surface counts per bed during 72h encompassing sampling days ( P  = 0.012). Conclusion: Passive air sampling provides quantitative data analogous to that obtained from surfaces. Settle plates could serve as a proxy for routine environmental screening to determine the infection risk in ICU.